2022
DOI: 10.1002/gps.5732
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in rate of force production during multifinger tasks are associated with cognitive status

Abstract: Objectives The multifinger force deficit (MFFD) is the decline in force generated by an individual finger as the number of fingers contributing to the action is increased. It has been proposed that as a measure of neural sufficiency rather than muscle status, it provides a means of detecting individuals at risk of cognitive decline. Age‐related deficits in central neural drive exert a disproportionate impact on the rate at which force can be generated. We examined whether a MFFD derived from the maximum rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Based on the correlation of −0.38 between the rofMFFD and MoCA obtained by Carson and Holton [ 21 ]; α = 0.05; power (1 − β error prob) = 0.80; a minimum sample size of 45 was estimated for the Kendall coefficient using the method of Looney [ 28 ]. Sixty-two volunteers took part in the study (42 females, 20 males, range 65–87, median 72.5 years) (see Supplementary Information).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the correlation of −0.38 between the rofMFFD and MoCA obtained by Carson and Holton [ 21 ]; α = 0.05; power (1 − β error prob) = 0.80; a minimum sample size of 45 was estimated for the Kendall coefficient using the method of Looney [ 28 ]. Sixty-two volunteers took part in the study (42 females, 20 males, range 65–87, median 72.5 years) (see Supplementary Information).…”
Section: Methodsmentioning
confidence: 99%
“…Corresponding calculations were undertaken to obtain the rofMFFD. This was the (mean) maximum rof generated in the multifinger condition, as a ratio of the (mean) maximum rof generated when that finger was used in isolation [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stronger grip forces have been associated with better cognitive performance in 527 patients between 45 and 62 years of age diagnosed with major depression (Firth, Smith, and Sarris, 2020). Multi-finger grip force deployment involves sophisticated neural control mechanisms (Kilgour, Todd, and Starr, 2014), and it has been suggested that decline in multi-finger grip strength is a marker of brain health (Carson and Holton, 2022). In healthy subjects (Cai et al , 2018) grip force is accurately scaled to just a little stronger than the minimum necessary to prevent the object from slipping out of the hand as a result of adaptive processes in finger force control during motor learning (Zatsiorsky and Latash, 2008;Cole, Potash, and Peterson, 2008).…”
Section: From Anthropometric Factors To Cognitive Fitnessmentioning
confidence: 99%